2017
DOI: 10.1007/s10552-017-0939-2
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and the risk of skin cancer: a prospective cohort study

Abstract: Purpose Endometriosis has been associated with an increased risk of skin melanoma. However, associations with other skin cancer types and how they compare with melanoma are unclear. Our objective was to prospectively investigate the relationships between endometriosis and risk of non-melanoma and melanoma skin cancers. Methods E3N is a prospective cohort of 98,995 French women aged 40–65 years in 1990. Data on surgically-confirmed endometriosis and skin cancer diagnoses were collected every 2–3 years through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 57 publications
1
11
2
2
Order By: Relevance
“…Unlike the previous studies, we found a slightly increased incidence of basal cell carcinoma in the entire cohort and in the sub‐cohorts of ovarian and peritoneal endometriosis . We speculate that this increase might in part be due to increased surveillance as endometriosis patients are likely to attend health care more often in comparison to the general public.…”
Section: Discussioncontrasting
confidence: 88%
“…Unlike the previous studies, we found a slightly increased incidence of basal cell carcinoma in the entire cohort and in the sub‐cohorts of ovarian and peritoneal endometriosis . We speculate that this increase might in part be due to increased surveillance as endometriosis patients are likely to attend health care more often in comparison to the general public.…”
Section: Discussioncontrasting
confidence: 88%
“…Среди других онкологических заболеваний наиболее часто связывают с эндометриозом неходжкинскую лимфому [6, 10, 11] и меланому кожи [6,10,11,29]. В небольших исследованиях также сообщалось, что женщины с эндометриозом подвергаются повышенному риску развития злокачественных опухолей органов эндокринной системы [11], головного мозга [11], рака щитовидной железы и почки [11,30], базальноклеточного рака [11,30].…”
Section: Discussionunclassified
“…When considering skin cancer type, endometriosis was associated with melanoma risk but not with SCC or BCC. Therefore, Leslie V. Farland et al confirm the association between endometriosis and the risk of skin cancer and suggest that this association is the strongest in melanoma [30].…”
Section: Non-gynecological Cancersmentioning
confidence: 90%